Effect of Ict Financial Services on the Performance of Commercial Banks in Uganda: Case Study Centenary Bank - Hope Mbabazi (Uganda Christian University, 2024)
The study assessed the impact of financial technology services adoption on the performance of commercial banks in Uganda, focusing on Centenary Bank, Mukono Branch. The study aimed to determine the extent to which automated teller machines (ATMs) enhance performance. Specifically, it sought to investigate the effect of online banking on the performance of Centenary Bank. A descriptive research design was employed, targeting a population of 60 employees, with a sample size of 47. Data were collected from both primary and secondary sources using questionnaires, interviews, and observations as the main instruments. The study revealed that most respondents use ATMS. The quality of the services has significantly improved. There are now much fewer queues in the banking halls, and wait times have been significantly decreased. Performance has been a relatively positive. Efficiency of service in form of withdraw and deposit money has improved. ATMs also save consumers time standing in line to deposit and take cash. The survey also found that consumers are proficient in using ATMs, which enhances the bank's operations. The results also showed that a significant proportion of employees were more driven to deliver quality service as a result of using online banking. The majority concurred that since customers can transact at any moment, many have always been able to check their most recent transactions and save time. As ICT improves service quality, provides constant and regular availability, lowers errors and data redundancies, and offers quick service delivery, the study suggested that banks encourage all of their clients to adopt ICT services. Technology is a crucial factor in ensuring that information systems are aligned with business strategy, thus banks should invest in and integrate it.